Современное состояние варакушки в Одесской области - Корзюков, А.И.; Трифонов, В.Г.; Коваль, Л.К. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 1999)
Материал собран на севере Одесской области в Балтском районе в 1985-1994 гг. Даты первого прилета варакушек на севере Одесской области: 6.04.85, 4.04.86, 8.04.87, 30.03.88, 18.03.89, 2.04.90,5.04.91, 7.04.92, 7.04.93, 2.04.94, в южных районах области 10.06.96 (Будакский лиман) и 2.04.99 (низовья Куяльницкого лимана). Самцы прилетают на 10-15 дней раньше самок. Матеріал зібрано на півночі Одеської області в Балтському районі в 1985-1994 рр. Дати першого прильоту синьошийок на півночі Одеської області: 6.04.85, 4.04.86, 8.04.87, 30.03.88, 18.03.89, 2.04.90,5.04.91, 7.04.92, 7.04.93, 2.04.94, в південних районах області 10.06.96 (Будакський лиман) і 2.04.99 (пониззя Куяльницького лиману). Самці прилітають на 10-15 днів раніше самок. Material was collected in the northern part of the Odessa region (the Balta district) in 1985-1994.The earliest arrival of liluethroats to the breeding area was observed on 18.03.89, the latest – on 8.04.87. Dates of the first spring observation of Bluethroats in the north of Odessa region are the following – 6.04.85, 4.04.86, 8.04.87, 30.03.88, 18.03.89, 2.04.90,5.04.91, 7.04.92, 7.04.93, 2.04.94. Dates of the first arrival in the southern areas are – 10.06.96 (Budakski Liman) and 2.04.99 (Liman of Kuyainik, the lower reaches). Mates arrive 10-15 days earlier than females.